COMMUNITY SERVICE ACTIVITIES (CSA): OPTIMIZING DIGITAL MARKETING STRATEGIES FOR THE DEVELOPMENT OF TEMPE HOME INDUSTRIES IN KARBUNGOH VILLAGE, SUKOLILO DISTRICT, MADURA ISLAND: Community Service Activities (Csa): Optimizing Digital Marketing Strategies For The Development Of Tempe Home Industries In Karbungoh Village, Sukolilo District, Madura Island - Putri, Erni Puspanantasari (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
This community service activity (CSA) aims to introduce and optimize digital marketing strategies for the development of the tempeh home industry in Karbungoh Village, Sukolilo District, Madura Island. The tempe home industry in this region has significant economic potential due to its reliance on local raw materials and the skills of the local community. However, limitations in promotion and utilization of digital technology have resulted in product marketing remaining conventional and limited market reach. Using a qualitative descriptive approach, this activity utilized observation, interviews, and direct mentoring of tempeh entrepreneurs to understand their actual conditions and marketing needs. The results of the activity indicated that entrepreneurs had a vision to become hygienic, high-quality, and highly competitive tempeh producers but lacked a structured digital strategy. Therefore, the community service team introduced a digital marketing strategy based on social media (Instagram, Facebook, and WhatsApp Business) and marketplaces (Shopee and Tokopedia) to expand market reach. Additionally, training was provided on promotional content creation, local product branding, and the development of a digital marketing evaluation plan. The implementation of this strategy is expected to increase competitiveness, strengthen the identity of local Madurese products, and open opportunities for expansion into modern markets. This activity is a concrete manifestation of the synergy between universities and the community in supporting digital transformation for micro-businesses in rural areas.